The little red fort - Maier, Brenda (Brenda J.) (Scholastic Press, 2018)
In this adaptation of the Little Red Hen fable, Ruby wants to build a fort, but her three brothers refuse to help, so when the fort is finished Ruby will not let them join her--until the boys come up with a few embellishments for the fort, like a mailbox, a garden, and a fresh coat of paint.